PENGARUH DISIPLIN KERJA, FASILITAS KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. HILON SUMATERA - Manullang, Winda Tetty Agustina; Sinaga, Ria Veronica; Silalahi, Esli (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2022)
This study aims to determine the extent of the influence of work discipline, work facilities and workload on employee performance at PT. Hilon Sumatera. Data was collected through questionnaires and documentation techniques. The research method used is quantitative, with 66 respondents taken using saturated sampling or census. Data analysis in this study using SPSS version 22.00. The results of the t-test indicate that the work discipline variable has a positive and significant effect on employee performance where the value of tcount (3.753 ) > t table (1.670) and a significant value of 0.000 < (0.05). Work facilities have a positive and significant effect on employee performance, it can be seen from the value of tcount (4.499) > ttable (1.670) and a significant value of 0.000 < (0.05). Workload has a positive and significant effect on employee performance, it can be seen from the value of tcount (2.426)> ttable (1.670) and a significant value of 0.018 < (0.05). The results of the F test indicate that work discipline, work failure and workload have a positive and significant effect on employee performance (Fcount of 72.834 > Ftable of 2.75). R square of 0.883 or 88.3% means that the variation in employee performance can be explained by the variables of work discipline, work facilities and workload of 88.3%, while another 11.7% is explained by other variables not included in this study. Preferably PT. Hilon Sumatera is increasingly improving the performance of its employees by providing adequate work facilities, such as machinery, infrastructure, inventory equipment, buildings, transportation equipment and work spaces. Employee work discipline needs to be improved by giving sanctions to employees who arrive late and do not comply with company regulations and the workload given is in accordance with the available working time so that production targets can be realized.